REACTIVE ARTHRITIS IN THE PEDIATRIC PRACTICE OF THE DONETSK REGION - Koniushevska, A.A.; Kuzevanova, M.V.; Herasymenko, Ye.O.; Gerasymenko, K.О.; Gerasymenko, V.V. (World of Medicine and Biology, 2024)
The article considers the features of reactive arthritis course in children. The results of a retrospective study of 482 children with reactive arthritis are presented. Most often, reactive arthritis was diagnosed in pre-school children. In more than 27 % of cases, children have a history of acute respiratory infections, in 69.5 % of cases the trigger is not determined. It was found that in most patients the disease had acute character. Among the clinical manifestations the most common lesions of the hip and knee joints were of monoarticular type, children did not have high levels of laboratory activity. Relapses of the disease are not excluded.
Keywords: reactive arthritis; children; clinical picture; diagnosis; treatment